2012
DOI: 10.1111/j.2042-7174.2012.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of pharmacist-delivered warfarin education in the home

Abstract: Use of an existing healthcare framework overcame several systemic barriers by facilitating warfarin education in patients' homes. While the intervention was associated with better short-term warfarin knowledge, follow-up may be required to optimise its benefits. Widespread implementation of home-based warfarin education by pharmacists has the potential to contribute significantly to improved outcomes from warfarin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 29 publications
1
31
1
Order By: Relevance
“…We postulate that one reason that the present study did not detect significant benefits from an education programme where others have, is that The Royal Melbourne Hospital already has a well‐established, pharmacy‐driven inpatient warfarin education programme. This suggests that where a good inpatient education system exists, a similar outpatient intervention would unlikely provide further benefit.…”
Section: Discussioncontrasting
confidence: 61%
“…We postulate that one reason that the present study did not detect significant benefits from an education programme where others have, is that The Royal Melbourne Hospital already has a well‐established, pharmacy‐driven inpatient warfarin education programme. This suggests that where a good inpatient education system exists, a similar outpatient intervention would unlikely provide further benefit.…”
Section: Discussioncontrasting
confidence: 61%
“…Six of the studies reported some statistical differences in baseline characteristics between their intervention and control groups . The majority ( n = 10) of studies clearly described the patient flow and where and why losses or drop‐out occurred . In most of these studies, the retention rate was ≥ 80%.…”
Section: Resultsmentioning
confidence: 99%
“…Only four trials reported utilizing existing pharmacist roles, with no further training or funding deemed necessary . The majority of the interventions ( n = 9) involved the community pharmacist making a home visit , one involved telephone communication , one was face‐to‐face interaction in the community pharmacy and three were unclear to the authors as they were not described in detail . These different forms of communication and interaction were performed in order to carry out a follow‐up interview to provide education, counselling, check adherence and medication issues, remove inappropriate/excess medications and provide information on laboratory monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The for health care professionals. The third section (assessment of counselling practice of healthcare professionals for patients on warfarin therapy and they were developed from published studies [20,21]. Data was collected by three volunteer pharmacists after pretested in 5% of study population to check for its clarity, simplicity, understand ability and coherency.…”
Section: Methodsmentioning
confidence: 99%